Η μεσοπολεμική πεζογραφία. Τόμος 4ος : από τον πρώτο ως τον δεύτερο παγκόσμιο πόλεμο 1914-1939 (Σοκόλης, 1996)
Γιώργος Θεοτοκάς -- Μαρία Ιορδανίδου -- Νίκος Καζαντζάκης -- Πάνος Καραβίας -- Μιχάλης Καραγάτσης -- Θράσος Καστανάκης